Criminology Towards the Metaverse: Cryptocurrency Scams, Grey Economy and the Technosocial. (7th February 2022) - Mackenzie, Simon
Abstract: Online markets in cryptocurrency represent a sprawling and eclectic alternative financial system, selling cutting edge techno-investment schemes that are complex and high risk. Crime control is almost entirely absent from this new crypto economy, and it is full of scams. This paper draws on an ethnography of crypto trading to review the main types of scam, suggesting that the grey economy of cryptocurrency trading is part of a wider evolution of society towards the technosocial, and beyond that perhaps towards the metaversal.